THYROID CARCINOSARCOMA - V. М. Perelmuter; S. А. Glushchenko; N. V. Vasilyev; Е. L. Choinzonov; М. R. Mukhamedov; D. Е. Kulbakin (Сибирский онкологический журнал)
A rare case of thyroid carcinosarcoma has been presented. Clinical features of progression of this rare disease have been described. The detailed assessment of the histological pattern of metastatic spread of thyroid carcinocarcoma has been given. The main causes of unfavorable outcome of this disease have been analyzed.